PROJECT METHOD IN STEM EDUCATION USING ARDUINO SOFTWARE AND HARDWARE PLATFORM - Voronkin, Oleksii; Lushchin, Sergiy (Physical and Mathematical Education, 2023)
Formulation of the problem. One of the promising methods of training in STEM education is the method of projects. The projected method in STEM education determines the relevance and research nature of the topic of the project, ensuring the interconnection of theoretical knowledge with practice, practical implementation of the results of the project. The project, as a means of implementing STEM education, allows you to integrate knowledge from different subject industries when solving real tasks, the creation of existing layouts, which causes their practical use. Materials and methods. Methods of analysis and systematization of scientific and pedagogical literature were used; generalization of the results of domestic and foreign experience in the use of a prose method in the STEM education using the ARDUino software and hardware platform. The experimental method of creating an active physiotherapy laser device for treatment of the runny nose is presented. A software modeling is used to simulate a device with the design of the Arduino Uno board. Results. The example of the implementation of the STEM project "Development of a physiotherapeutic laser device for the treatment of runny nose" demonstrates how it is possible to integrate many different-level, didactic, and research tasks. A generalized description of the main structural elements of the Arduino Uno board is given. A typical algorithm for familiarizing yourself with the operation of the Arduino board is formulated. The main sections of the physics course are indicated, the knowledge of which is fundamental for implementing the project. It is shown how using a bit matrix of laser states allows the creation of cyclic irradiation modes that periodically change each other. An example of a code processing a bit matrix of laser states is provided. The sketch controls the modes of the semiconductor laser, displays the exposure time on the liquid crystal display, and emits a sound signal at the end of the exposure time set by the potentiometer. A fragment of the simulation modeling of a physiotherapy device in the Tinkercad Circuits environment is presented. Conclusions. The practical experience of using the project method in STEM education has shown that it allows students to investigate a real problem actively, apply the acquired knowledge in practice, and develop cooperation, communication, and critical thinking skills. Implementation of the project contributes to the combination of various activities, such as cognitive, creative, practical, and research, as well as the development of thinking skills, motivation, and responsibility for one’s actions. Implementing the project method makes it possible to provide high-quality training for specialists in natural sciences who can effectively apply their knowledge and skills in practical situations and contribute to the further development of STEM fields in Ukraine.